The prevalence of stress among medical students in Syria and its association with social support: a cross-sectional study - Hasan Nabil Al Houri; Sami Jomaa; Douaa Mohammad Nazir Arrouk; Tarek Nassif; Marina J Al Ata Allah; Ahmad Nabil Al Houri; Youssef Latifeh (BMC Psychiatry, 2023)
Abstract Introduction Chronic stress can interrupt personal life and cause fatigue, inability to concentrate, and irritability. This study aims to determine the prevalence of stress and its associated factors among medical students in Syria and whether social support could be a protective factor against stress. Methods A cross-sectional study was conducted in the faculty of medicine of five Syrian universities. The Medical Student Stressor Questionnaire (MSSQ) was used to evaluate the stress caused by the possible sources of stress. And Social Support Questionnaire – short version (SSQ – short version) was used to assess the social support that medical students received from family, friends, and their fellow medical students using six questions. Results A total of 1472 medical students participated in the study. Among the total participants, 671 (45.6%) were males, and 801 (54.4%) were females. The majority of the participators had mild (50.6%; n = 745) and moderate (37.0%; n = 545) stress levels. Academic-related stressors were the most important cause of stress among undergraduate medical students. Social support was provided equally to both genders, and genders reported the same degree of satisfaction. Conclusion Our results emphasize the importance of improving the curricula, providing mental health consultants for students, and paying more attention to the mental health of female students. Finally, students in their clinical years should also receive mental health care, decreasing their duties and providing more self-free time.